Pendampingan Kelompok Pemberdayaan Kesejahteraan Keluarga (PKK) Desa Pagaruyung, Kecamatan Tapung, Kabupaten Kampar sebagai Desa Wirausaha dalam Inovasi Produk Olahan Sirup Nanas - Yusmarini, Yusmarini; Dewi, Yossie Kharisma; Ayu, Dewi Fortuna; Riftyan, Emma; Hasnah, Nur; Maulida, Yusni; Siswanto, Siswanto; Nugroho, Wahyu Satrio; Putri, Cahya Dwi; Harahap, Hamdan Fauzi; Agustina, Hylda Putri; Firmansyah, M. Hafiddin; Susanti, Dewi Susi; Gussamwang, Muhammad; Harvey, Edwardo; Va, Hanny Sc; Apriani, Imelda Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Pagaruyung Village is the largest pineapple producer in Kampar Regency with sales of 10.330 tons per year. The main problem faced by Pagaruyung Village as a pineapple producing center is that most of the pineapples produced are sold fresh at low prices, around Rp. 3,000-5,000 per fruit, so that there are often several obstacles in the distribution of fresh pineapples related to quality, storage, and transportation. Pineapples can be processed into other processed products such as syrup. Syrup is a processed food product that has a long shelf life and a simple production stage. Pineapple syrup can be an effective solution as well as a characteristic of the village to attract local and international tourists, as well as support independent food security efforts.The aim of the community service program through mentoring activities is that Pagaruyung Village, Tapung District, can become an entrepreneurial village in order to create an independent village and improve the economy of village communities through synergy between Riau University as a university and assisted villages within the scope of Riau Province. In this activity, an approach was taken through socialization regarding various processed products made from pineapple, direct practice in making pineapple syrup using simple technology, as well as evaluating activities using a questionnaire. The results of this training reveal the community's innovation and enthusiasm in processing pineapple into pineapple syrup. To achieve the main goal, namely improving the local economy and making Pagaruyung Village a tourist destination, ongoing coaching and training efforts are needed.